Temperature and pH dual-responsive self-adapting swelling microspheres for cementing plugging and preparation method thereof

CN123003178APending Publication Date: 2026-10-30JIAHUA SPECIAL CEMENT
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611146241.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-30
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

其中,刚性颗粒依靠粒径匹配形成架桥封堵,但对裂缝宽度变化的适应性有限;纤维材料可增强封堵层结构,但单独使用难以有效填充微孔隙;普通吸水膨胀材料具有一定填充能力,但在水泥浆或钻井液中易提前吸水膨胀,导致浆体黏度升高、流动度下降,甚至引发泵送困难和堵管风险

Benefits of technology

1.本发明通过相变延迟响应层和硅烷偶联改性外层的协同作用,有效控制水分进入吸水膨胀基体的速率。相变延迟响应层在低温条件下呈固态疏水或半疏水屏障,对水分进入微球内部形成物理阻隔;硅烷偶联改性外层通过形成表面硅氧烷改性薄层,进一步延缓水分初期侵入。二者协同作用,使微球在25~35℃、pH 12~13的强碱性水泥浆环境中2 h内膨胀倍率不超过1.5倍,避免地面配浆和泵送阶段提前膨胀,不会明显增加水泥浆黏度,也不会导致流动度骤降,有效保证水泥浆的流动性和可泵送性,确保施工安全。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application discloses a temperature-sensitive-pH dual-response self-adaptive expansion microsphere for cementing plugging and a preparation method. The expansion microsphere comprises, from inside to outside, a water-absorbing expansion matrix, a phase change delay response layer and a silane coupling modified outer layer, and the phase change delay response layer is dispersed with a thermal expansion inner core. The water-absorbing expansion matrix is composed of a crosslinked copolymer of acrylic acid and acrylamide; the melting point of the phase change delay response layer is 45-100 DEG C; and the silane coupling modified outer layer is the outermost layer of the expansion microsphere. The application controls the moisture entering rate through the phase change delay response layer and the silane coupling modified outer layer, so that the expansion microsphere has an expansion ratio of not more than 1.5 times within 2 hours under the environment of 25-35 DEG C and pH 12-13; after entering the leakage layer, the expansion microsphere gradually expands under the action of the downhole temperature rise and the formation water, fills the residual channels of the cracks; the silane coupling modified outer layer enhances the interfacial bonding force between the microsphere and the cement stone, and improves the long-term stability and pressure-bearing capacity of the plugging layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of plugging materials for oil and gas well engineering, specifically to a temperature-sensitive-pH dual-response self-adaptive expanding microsphere for cementing and plugging, and its preparation method. Background Technology

[0002] During cementing and drilling of oil and gas wells, fractured, broken, dissolved, and depleted formations are prone to leakage. Traditional plugging materials mainly include rigid particles, fiber materials, sheet materials, water-absorbing resins, and expanding particles. Among them, rigid particles rely on particle size matching to form bridging and plugging, but their adaptability to changes in fracture width is limited; fiber materials can enhance the plugging layer structure, but are difficult to effectively fill micropores when used alone; ordinary water-absorbing expanding materials have a certain filling capacity, but they tend to absorb water and expand prematurely in cement slurry or drilling fluid, leading to increased slurry viscosity, decreased fluidity, and even pumping difficulties and pipe blockage risks.

[0003] Existing temperature-sensitive plugging materials mostly rely on temperature-triggered expansion, but their response temperature is singular, failing to balance the safety of surface slurry preparation and the effectiveness of downhole plugging. While pH-responsive materials can change volume according to variations in the acidity or alkalinity of formation fluids, they tend to swell prematurely in strongly alkaline cement slurries, making them unsuitable for cementing operations. Therefore, there is a need to develop an intelligent plugging material that remains stable during both surface and wellbore pumping phases and expands rapidly and controllably after entering lost circulation fractures. Summary of the Invention

[0004] To address the aforementioned technical problems, this invention provides a temperature- and pH-responsive self-adaptive expandable microsphere for cementing and plugging. Through structural design, this invention enables the expandable microspheres to maintain a delayed expansion state in a low-temperature, strongly alkaline environment, and to gradually expand in response to changes in downhole temperature, pH, and formation water, filling residual channels in fractures, thereby improving the plugging rate, pressure-bearing capacity, and long-term stability.

[0005] To achieve the above objectives, the technical solution adopted by the present invention is as follows: The first aspect of the present invention provides a temperature-sensitive-pH dual-response self-adaptive expandable microsphere for cementing and plugging, comprising a water-absorbing expandable matrix, a phase change delayed response layer and a silane coupling modified outer layer arranged sequentially from the inside to the outside, wherein a thermally expandable core is dispersed in the phase change delayed response layer. The water-absorbing and swelling matrix is ​​a microsphere core layer composed of a crosslinked copolymer of acrylic acid and acrylamide. Based on a total mass of 100 parts of acrylic acid and acrylamide, the raw material composition of the water-absorbing and swelling matrix is: 55-80 parts of acrylic acid, 20-45 parts of acrylamide, 0.10-0.50 parts of crosslinking agent, 0.20-1.00 parts of initiator, and a pH adjuster to achieve a neutralization degree of 50%-80% for acrylic acid. The phase change delayed response layer is coated on the surface of the water-absorbing and swelling matrix and partially penetrates into the surface pores of the water-absorbing and swelling matrix. The melting point of the phase change delayed response layer is 45~100℃, and the phase change delayed response layer accounts for 5%~25% of the total mass of the swelling microspheres. The thermally expanded core is dispersed in the phase change material of the phase change delayed response layer, and the thermally expanded core accounts for 1% to 10% of the total mass of the expanded microspheres; The silane coupling modified outer layer is the outermost layer of the expanded microspheres, covering the surface of the phase change delayed response layer. It is formed by modifying the surface of the expanded microspheres with a silane coupling agent, and the amount of silane coupling agent is 0.2% to 3.0% of the mass of the expanded microspheres.

[0006] Furthermore, the mass ratio of acrylic acid to acrylamide is 6:4 to 8:2; the crosslinking agent is N,N'-methylenebisacrylamide; the initiator is any one or more of ammonium persulfate, potassium persulfate, sodium bisulfite-ammonium persulfate redox initiation system, or azo initiators, wherein the mass ratio of ammonium persulfate to sodium bisulfite in the sodium bisulfite-ammonium persulfate redox initiation system is 1:0.2 to 1:0.6; and the pH adjuster is sodium hydroxide, potassium hydroxide, or ammonia.

[0007] Furthermore, the phase change delayed response layer has a melting point of 55~90℃ and accounts for 8%~18% of the total mass of the expanded microspheres; the phase change delayed response layer is composed of one or more phase change materials selected from paraffin wax, microcrystalline wax, polyethylene wax, carnauba wax, stearic acid, ethylene-vinyl acetate copolymer wax and melting point adjustable composite wax.

[0008] Furthermore, the thermally expanding core accounts for 2% to 6% of the total mass of the expanded microspheres; the thermally expanding core consists of azo-based thermally decomposed gas-generating materials, a bicarbonate-weak acid slow-release gas-generating system, and Low-boiling-point organic expanding agents The system comprises one or more materials, including thermally expandable microcapsules encapsulated in phase change materials; the bicarbonate-weak acid sustained-release gas-producing system comprises sodium bicarbonate, potassium bicarbonate or ammonium bicarbonate, and citric acid, tartaric acid, gluconic acid, adipic acid, or weak acid particles coated with wax / resin, wherein the mass ratio of bicarbonate to weak acid is 1:0.2 to 1:1.5; the thermally expandable microcapsules are microcapsules with acrylonitrile copolymers, vinylidene chloride copolymers, methacrylate copolymers or their complexes as the shell and a low-boiling-point organic expander as the core material, wherein the initial expansion temperature of the thermally expandable microcapsules is 60 to 120°C; the azo thermal decomposition gas-producing material is azobisisobutyronitrile, azodicarbonamide, azobisisobutyronitrile or / and azodicarbonamide modified products; the low-boiling-point organic expander is isopentane, isobutane, isooctane, or petroleum ether fraction.

[0009] Furthermore, the silane coupling agent is one or more of KH550, KH560, and KH570; the amount of silane coupling agent used is 0.5% to 1.5% of the mass of the expanded microspheres.

[0010] The second aspect of this invention also provides a method for preparing the above-mentioned temperature-sensitive-pH dual-responsive self-adaptive expandable microspheres for cementing and plugging, comprising the following steps: S1. Mix acrylic acid and acrylamide in a mass ratio, add deionized water and stir to dissolve, so that the total mass of acrylic acid and acrylamide accounts for 35% of the total mass of the solution, to obtain a monomer solution; add a crosslinking agent to the monomer solution; then slowly add a pH adjuster to make the degree of neutralization of acrylic acid reach 50%~80%, and the pH of the system after neutralization is 6.0~8.0. Purify with nitrogen for 10~30 minutes, then add an initiator to obtain an aqueous phase; S2. Heat the phase change material to a molten state; add the thermal expansion core to the molten phase change material, stir and disperse to form a phase change pre-dispersion liquid containing the thermal expansion core; wherein, the mass ratio of the phase change material to the thermal expansion core is 100:5~100:40. S3. Using an oily solvent as the continuous oil phase, add an emulsifier and stir until the emulsifier is completely dissolved to obtain the oil phase; wherein, the amount of emulsifier is 1.0%~5.0% of the mass of the continuous oil phase; S4. Slowly add the aqueous phase obtained in step S1 to the oil phase obtained in step S3, controlling the volume ratio of the aqueous phase to the oil phase to be 1:2~1:6; stir and disperse at 300~600 r / min to form a W / O type reverse suspension polymerization system; heat to 55~75℃ and react for 3~6 h to allow acrylic acid and acrylamide to crosslink and copolymerize, forming crosslinked water-absorbing microspheres. S5. After washing, filtering and pre-drying the cross-linked water-absorbing microspheres obtained in step S4 to a water content of 8%~15%, add them to the phase change pre-dispersion liquid containing the thermally expanded core obtained in step S2. The mass ratio of the cross-linked water-absorbing microspheres to the phase change pre-dispersion liquid containing the thermally expanded core is 100:8~100:22. Stir and coat for 10~60 min. Then cool and solidify to allow the phase change material and the thermally expanded core to adhere to the surface of the water-absorbing and expanding matrix and embed into its surface pores, forming composite microspheres with delayed response function. S6. Immerse the composite microspheres obtained in step S5 in a silane coupling agent solution composed of silane coupling agent, ethanol, and water, wherein the mass of the silane coupling agent accounts for 0.5% to 2.0% of the total mass of the silane coupling agent solution, and the volume ratio of ethanol to water is 90:10; adjust the pH of the silane coupling agent solution to 4 to 5 with acetic acid to promote silane hydrolysis for 20 to 30 min; then let it stand and soak at room temperature for 0.5 to 3 h; after removal, filter, and dry for 6 to 12 h at a temperature 5 to 20°C below the melting point of the phase change delayed response layer to obtain temperature-sensitive-pH dual-response self-adaptive expanding microspheres; S7. The dried expanded microspheres are sieved to obtain expanded microspheres with a particle size of 0.1~1.0 mm.

[0011] Further, in step S2, the mass ratio of phase change material to thermal expansion core is 100:10 to 100:25; in step S3, the oily solvent is liquid paraffin, white oil, cyclohexane or isooctane, the emulsifier is sorbitan monooleate, and the amount of emulsifier is 1.5% to 3.0% of the mass of the continuous oil phase; in step S4, the volume ratio of aqueous phase to oil phase is 1:3 to 1:5.

[0012] Further, in step S4, the mixture is stirred and dispersed at 350~500 r / min, heated to 60~70℃, and reacted for 4~5 h.

[0013] Furthermore, in step S6: the mass of the silane coupling agent accounts for 1.0% of the total mass of the silane coupling agent solution; and the solution is left to stand and soak at room temperature for 1-2 hours.

[0014] Further, in step S7, expanded microspheres with a particle size of 0.2–0.5 mm are obtained.

[0015] Compared with the prior art, the present invention has the following beneficial effects: 1. This invention effectively controls the rate at which moisture enters the water-absorbing and swelling matrix through the synergistic effect of a phase change delayed response layer and a silane coupling-modified outer layer. The phase change delayed response layer acts as a solid hydrophobic or semi-hydrophobic barrier at low temperatures, physically preventing moisture from entering the microspheres. The silane coupling-modified outer layer further delays initial moisture intrusion by forming a thin siloxane-modified surface layer. The synergistic effect of these two layers ensures that the expansion ratio of the microspheres does not exceed 1.5 times within 2 hours in a strongly alkaline cement slurry environment at 25-35℃ and pH 12-13. This prevents premature expansion during ground preparation and pumping, avoids a significant increase in cement slurry viscosity, and prevents a sudden drop in fluidity, effectively ensuring the fluidity and pumpability of the cement slurry and guaranteeing construction safety.

[0016] 2. After entering the lost-flow fracture, the microspheres (0.1~1.0 mm) are easily retained between bridging particles or in narrow fracture sections, allowing them to initially act as flexible particles to fill the gaps and reduce the seepage capacity of the fracture channels. As the downhole temperature rises above the melting point of the phase change delayed response layer, the phase change material softens and melts, and water gradually seeps into the water-absorbing and swelling matrix. The acrylic acid-acrylamide copolymer network endows the microspheres with excellent pH and ionic strength sensitive water absorption response: the carboxyl / carboxylate groups in the acrylic structural units have different degrees of dissociation and charge shielding under different pH and ionic strength conditions, thereby changing the osmotic pressure difference inside and outside the gel network, causing the microspheres to exhibit pH and mineralization sensitive water absorption and swelling behavior. Under the combined effects of increased downhole temperature, softening of the phase change delayed response layer, and continuous infiltration of formation water, the microspheres can expand by more than 4 times, effectively filling the pores and residual channels between the fracture bridging particles and achieving self-adaptive sealing of the fractures.

[0017] 3. The silane coupling-modified outer layer not only delays hydration under surface conditions, but also, after downhole expansion and plugging, the active groups (such as epoxy and amino groups) on the silane coupling agent can significantly improve the interfacial bonding force between the microspheres and cement stone through silanol condensation, hydrogen bonding, coordination adsorption, and mechanical embedding of cement hydration products (such as Ca(OH)2 and CSH gel). As the cement slurry gradually hydrates and hardens, the microspheres are firmly fixed in the plugging layer composed of cement stone and plugging particles compounded with cement stone, reducing interfacial peeling and the formation of seepage channels, and improving the long-term stability and pressure-bearing capacity of the plugging layer.

[0018] 4. This invention, through the selection of the melting point of the phase change delayed response layer and the introduction of a thermal expansion core, is applicable to a wide temperature range of downhole environments from 40 to 130°C. The melting point of the phase change delayed response layer can be adjusted within the range of 45 to 100°C according to the circulating temperature of the target well section and the static temperature of the lost circulation zone to meet the needs of different geothermal gradients at different well depths. After the temperature rises, the thermal expansion core softens in the phase change layer and forms local micropores or expansion channels, thereby promoting the entry of formation water into the water-absorbing and expanding matrix and improving the adhesion and filling ability of microspheres to fracture walls and bridging particle gaps. Simultaneously, this invention maintains effective expansion capacity in high-salinity formation water. Detailed Implementation

[0019] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. Obviously, the described embodiments are merely some embodiments of this invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.

[0020] Example 1, as a preferred embodiment of the present invention, discloses a temperature-sensitive-pH dual-response self-adaptive expandable microsphere for well cementing and plugging and its preparation method.

[0021] In this embodiment, the water-absorbing and swelling matrix is ​​a microsphere core layer composed of a crosslinked copolymer of acrylic acid and acrylamide. Based on a total mass of 100 parts of acrylic acid and acrylamide, the raw material composition is as follows: 70 parts of acrylic acid, 30 parts of acrylamide, 0.25 parts of crosslinking agent (N,N'-methylenebisacrylamide), 0.50 parts of initiator (ammonium persulfate), and a pH adjuster (NaOH solution) to achieve a neutralization degree of 70% for acrylic acid.

[0022] In this embodiment, the phase change delayed response layer accounts for 12% of the total mass of the expanded microspheres; the phase change delayed response layer is composed of a composite wax with a melting point of 55°C.

[0023] In this embodiment, the thermal expansion core accounts for 3% of the total mass of the expanded microspheres. The thermal expansion core is composed of thermal expansion microcapsules with an initial expansion temperature of about 60°C. The thermal expansion microcapsules have an acrylonitrile copolymer as the shell and isopentane low-boiling-point hydrocarbons as the core material.

[0024] In this embodiment, the silane coupling modified outer layer is formed by modifying the surface of the expanded microspheres with a silane coupling agent. The silane coupling agent is KH560, and the amount used is 1.0% of the mass of the expanded microspheres.

[0025] The preparation method in this embodiment is as follows: S1. Mix acrylic acid and acrylamide in a ratio of 70 parts:30 parts, add deionized water and stir to dissolve, so that the total mass of acrylic acid and acrylamide accounts for 35% of the total mass of the solution, to obtain a monomer solution; add 0.25 parts of crosslinking agent (N,N'-methylenebisacrylamide) to the monomer solution; then slowly add pH adjuster (NaOH solution) to make the degree of neutralization of acrylic acid reach 70%, the pH of the system after neutralization is 7.0, purge with nitrogen for 20 minutes to remove oxygen, and then add 0.50 parts of initiator (ammonium persulfate) to obtain an aqueous phase; S2. Heat the phase change material (composite wax with a melting point of 55℃) to a molten state; add the thermally expanded core material to the molten phase change material, stir and disperse to form a phase change pre-dispersion liquid containing the thermally expanded core; wherein, the mass ratio of the phase change material to the thermally expanded core is 100:25. S3. Using 400 mL of an oily solvent (liquid paraffin) as the continuous oil phase, add an emulsifier (sorbitan monooleate, Span 80) and stir until the emulsifier is completely dissolved to obtain the oil phase; wherein, the amount of emulsifier used is 2.0% of the mass of the continuous oil phase; S4. Slowly add the aqueous phase obtained in step S1 to the oil phase obtained in step S3, controlling the volume ratio of the aqueous phase to the oil phase to be 1:4; stir and disperse at 400 r / min to form a W / O type reverse suspension polymerization system; heat to 65℃ and react for 4 h to allow acrylic acid and acrylamide to crosslink and copolymerize, forming crosslinked water-absorbing microspheres. S5. After washing, filtering and pre-drying the cross-linked water-absorbing microspheres obtained in step S4 to a water content of 8%~15%, add them to the phase change pre-dispersion liquid containing the thermally expanded core obtained in step S2. The mass ratio of the cross-linked water-absorbing microspheres to the phase change pre-dispersion liquid containing the thermally expanded core is 100:15. Stir and coat for 30 min. Then cool and solidify to allow the phase change material and the thermally expanded core to adhere to the surface of the water-absorbing and expanding matrix and embed into its surface pores, forming composite microspheres with delayed response function. S6. Immerse the composite microspheres obtained in step S5 in a silane coupling agent solution composed of silane coupling agent, ethanol and water, wherein the mass of the silane coupling agent accounts for 1.0% of the total mass of the silane coupling agent solution, and the volume ratio of ethanol to water is 90:10; adjust the pH of the silane coupling agent solution to 4-5 with acetic acid to promote silane hydrolysis for 20-30 min; then let it stand and soak for 2 h at room temperature; after taking it out, filter it and dry it at 40℃ (below the melting point of the composite wax 55℃) for 12 h to obtain temperature-sensitive-pH dual-responsive self-adaptive expanding microspheres; S7. The dried expanded microspheres are sieved to obtain expanded microspheres with a particle size of 0.2~0.5 mm.

[0026] Example 2, as a preferred embodiment of the present invention, discloses a temperature-sensitive-pH dual-response self-adaptive expandable microsphere for cementing and plugging and its preparation method.

[0027] The difference between this embodiment and Embodiment 1 is that: Based on a total mass of 100 parts of acrylic acid and acrylamide, the raw material composition of the water-absorbing and swelling matrix is ​​as follows: 65 parts of acrylic acid, 35 parts of acrylamide; 0.35 parts of crosslinking agent (N,N'-methylenebisacrylamide); 0.60 parts of initiator (potassium persulfate); and pH adjuster (NaOH solution) to achieve a neutralization degree of 65% for acrylic acid.

[0028] The phase change delayed response layer accounts for 16% of the total mass of the expanded microspheres and is composed of composite microcrystalline wax with a melting point of 78℃.

[0029] The thermal expansion core accounts for 4% of the total mass of the expanded microspheres. The thermal expansion core is a thermal expansion microcapsule with an initial expansion temperature of about 80℃.

[0030] The silane coupling modified outer layer is formed by modifying the surface of the expanded microspheres with a silane coupling agent, KH560, and the amount used is 1.2% of the mass of the expanded microspheres.

[0031] In the preparation method: the oil solvent is 450 mL of white oil, and the amount of emulsifier (sorbitan monooleate, Span80) is 2.5% of the mass of the oil phase; the temperature is raised to 68℃ and reacted for 5 h to allow acrylic acid and acrylamide to crosslink and copolymerize, forming crosslinked water-absorbing microspheres; after being removed from S6, the microspheres are filtered and dried at 60℃ (lower than the composite microcrystalline wax 78℃) for 8 h.

[0032] Other conditions are the same as in Example 1.

[0033] Example 3, as a preferred embodiment of the present invention, discloses a temperature-sensitive-pH dual-response self-adaptive expandable microsphere for cementing and plugging and its preparation method.

[0034] The difference between this embodiment and Embodiment 1 is that: Based on a total mass of 100 parts of acrylic acid and acrylamide, the raw material composition of the water-absorbing and swelling matrix is ​​as follows: 72 parts of acrylic acid, 28 parts of acrylamide; 0.30 parts of crosslinking agent (N,N'-methylenebisacrylamide); 0.65 parts of initiator (sodium bisulfite-ammonium persulfate redox initiation system, of which ammonium persulfate is 0.45 g and sodium bisulfite is 0.2 g); and pH adjuster (NaOH solution) to achieve a degree of neutralization of acrylic acid of 68%.

[0035] The phase change delayed response layer accounts for 14% of the total mass of the expanded microspheres and is composed of a composite wax with a melting point of 68°C.

[0036] The thermal expansion core accounts for 3.5% of the total mass of the expanded microspheres. The thermal expansion core is composed of weak acid particles of sodium bicarbonate-citric acid slow-release gas production coated with microcrystalline wax, wherein the mass ratio of sodium bicarbonate to citric acid is 1:0.5.

[0037] The silane coupling modified outer layer is formed by modifying the surface of the expanded microspheres with a silane coupling agent. The silane coupling agent is a mixture of KH550 and KH560 in a mass ratio of 1:1, and the amount used is 1.0% of the mass of the expanded microspheres.

[0038] In the preparation method: the amount of emulsifier (sorbitan monooleate, Span80) is 2.2% of the oil phase mass; the temperature is raised to 60℃ and the reaction is carried out for 4.5 h to allow acrylic acid and acrylamide to crosslink and copolymerize, forming crosslinked water-absorbing microspheres; in S6, after being taken out and filtered, it is dried at 58℃ (lower than the composite microcrystalline wax 68℃) for 10 h.

[0039] Other conditions are the same as in Example 1.

[0040] Comparative Example 1 differs from Example 1 in that it only includes a water-absorbing and swelling matrix, without introducing a phase change delayed response layer, a thermally expanding core, and a silane coupling modified outer layer. Steps S2, S5, and S6 are omitted in the preparation method, and drying and sieving are performed directly after step S4. Other conditions are the same as in Example 1.

[0041] Comparative Example 2 differs from Example 1 in that it only contains a phase change delayed response layer and a thermal expansion core, excluding the water-absorbing and swelling matrix and the silane coupling modified outer layer. In this comparative example, the phase change material is a composite wax with the same melting point of 55°C as in Example 1; the thermal expansion core is a thermal expansion microcapsule with the same initial expansion temperature of approximately 60°C as in Example 1, using an acrylonitrile copolymer as the shell and isopentane-based low-boiling hydrocarbons as the core material.

[0042] The preparation method is as follows: S1, None (excluding water-absorbing and swelling matrix).

[0043] S2. Heat the phase change material (composite wax with a melting point of 55℃) to a molten state; add the thermal expansion core to the molten phase change material, stir and disperse to form a phase change pre-dispersion liquid containing the thermal expansion core; wherein, the mass ratio of the phase change material to the thermal expansion core is 100:25.

[0044] S3. Using an oily solvent (liquid paraffin) as the continuous oil phase, add an emulsifier (sorbitan monooleate, Span80) and stir until the emulsifier is completely dissolved to obtain the oil phase; wherein, the amount of emulsifier is 2.0% of the mass of the continuous oil phase.

[0045] S4. Slowly add the phase change predispersant obtained in step S2 to the oil phase obtained in step S3, controlling the volume ratio of the phase change predispersant to the oil phase to be 1:4; stir and disperse at 400 r / min to form a suspension system.

[0046] S5. The suspension system obtained in step S4 is gradually cooled and solidified into paraffin-based composite particles; then filtered and separated, and quickly washed with ethanol.

[0047] S6. Place the washed paraffin-based composite particles at 40℃ (55℃ below the melting point of the composite wax) and dry for 12 hours.

[0048] S7. The dried paraffin-based composite particles are sieved to obtain paraffin-based composite particles with a particle size of 0.2 to 0.5 mm.

[0049] Other conditions are the same as in Example 1.

[0050] Comparative Example 3 differs from Example 1 in that it does not contain a thermal expansion core. In step S2, no thermal expansion core is added to the phase change material, and the cross-linked water-absorbing microspheres are directly coated with molten phase change material.

[0051] Other conditions are the same as in Example 1.

[0052] Comparative Example 4 differs from Example 1 in that: the outer layer treatment of silane coupling modification is not performed, the silane coupling agent solution soaking treatment in step S6 is omitted, and the product is directly dried and sieved after step S5.

[0053] Other conditions are the same as in Example 1.

[0054] For the test examples, the expansion ratio performance of the above embodiments and comparative examples was tested. To ensure the reliability of the test results, each group of samples was tested in triplicate using the same batch of expanded microspheres. The test results are expressed as average values, as shown in Table 1. Note: High-mineralized brine is simulated formation water with a total mineralization of 150,000 mg / L.

[0055] Table 1. Expansion ratios (times) of each embodiment and comparative example under different conditions.

[0056] The results in Table 1 show that the present invention obtained in the embodiments can adapt to leak sealing operations under different temperature environments, with excellent expansion effect and better delayed expansion and temperature stability.

[0057] Comparative Example 1 (water-absorbing and swelling matrix only) swelled to 2.8 times its original size in 2 hours at 25°C and pH 13, while Example 1 only swelled to 1.12 times under the same conditions. The swelling ratio of Comparative Example 1 is approximately 2.5 times that of Example 1, indicating that without the protection of the phase change delayed response layer and the silane coupling modified outer layer, moisture rapidly enters the microspheres under a strongly alkaline environment at room temperature, leading to premature water absorption and swelling. This conclusion directly verifies the necessity of the phase change delayed response layer and the silane coupling modified outer layer for delayed expansion.

[0058] Comparative Example 2 showed an expansion ratio of only 3.2 times at 80°C and pH 10 for 24 hours, and only 4.0 times at 120°C for 24 hours. In contrast, Example 1 showed an expansion ratio of 8.6 times at 80°C and pH 10 for 24 hours, and Example 2 showed an expansion ratio of 9.4 times at 120°C and pH 10 for 24 hours. The expansion ratio of Comparative Example 2 was only about 1 / 2.4 to 1 / 2.7 of that of the Examples. This indicates that without the contribution of the water-absorbing network of the water-absorbing swelling matrix, the gas-generating expansion of the thermal expansion core alone cannot provide sufficient volume change, resulting in a severely insufficient expansion ratio. This conclusion directly verifies the necessary contribution of the water-absorbing swelling matrix to the main expansion volume.

[0059] Comparative Example 3 showed an expansion ratio of 1.15–1.32 times after 2 hours at 25–35°C and pH 13, which was basically the same as that of Example 1, indicating that the delay effect of the phase change layer and the silane outer layer remained good even without the thermal expansion core. However, at high temperatures of 60–120°C, the expansion ratio (3.9–7.8 times) was lower than that of the corresponding examples (4.8–9.6 times), especially in the 100–120°C range, where the difference was more significant (7.3–7.8 times for Comparative Example 3 and 8.1–9.6 times for Examples 1 and 2). This indicates that without the thermal expansion core to provide supplementary expansion driving force at high temperatures, the expansion capacity of the water absorption network itself is reduced at high temperatures due to its temperature and pH response alone. This conclusion verifies the supplementary enhancement effect of the thermal expansion core at high temperatures.

[0060] Comparative Example 4, under conditions of 25–35°C and pH 13, showed an expansion ratio of 1.45–1.75 times after 2 hours, higher than Example 1 (1.12–1.28 times). This indicates that without the auxiliary water-blocking effect of the silane outer layer, the physical barrier of the phase change layer alone accelerated the water intrusion rate and slightly reduced the delay effect. This demonstrates that the silane coupling-modified outer layer plays a necessary role in further reducing the initial water absorption and expansion in strong alkaline cement slurry. Under high-temperature conditions of 60–120°C, the expansion ratio of Comparative Example 4 was basically the same as or even slightly higher than that of the Example, indicating that the effect of the silane outer layer at high temperatures is mainly reflected in interfacial bonding rather than the expansion ratio itself.

[0061] In an application example, the temperature-sensitive and pH-responsive expandable microspheres prepared in Example 1 were added to the cementing slurry at a rate of 3% to 6% of the oil well cement mass. Initial flowability and 30-minute flowability were tested according to the relevant methods in GB / T 19139. The basic formula of the cementing slurry is as follows: 100 parts of Grade G oil well cement, 10 parts of silica fume, 0.8 parts of dispersant, 0.2 parts of defoamer, 45 parts of water, 10 parts of plugging particles, and 4 parts of the expandable microspheres of this invention.

[0062] In comparison, ordinary expanding particles (commercially available polyacrylate water-absorbing and expanding plugging particles) were added to the above cementing slurry formulation in the same amount, and a performance comparison test was conducted. The test results are shown in Table 2.

[0063] Table 2 Performance test results of application examples

[0064] Table 2 shows that the flowability of the cement slurry with the microspheres of this invention was 22.0 cm after 30 minutes, an increase of 5.5 cm compared to the control group (16.5 cm), indicating that the microspheres of this invention did not expand significantly during the pumping stage, ensuring the fluidity of the slurry; the sealing rates of 3 mm and 6 mm cracks reached 98.6% and 96.9%, respectively, an increase of 10.2 and 15.7 percentage points compared to the control group; the leakage at 5 MPa was only 16 mL, a decrease of 76% compared to the control group (68 mL), significantly improving the pressure-bearing capacity. The results indicate that the microspheres of this invention balance the safety of surface construction with the effectiveness of downhole sealing.

[0065] Finally, it should be noted that the above embodiments are merely preferred embodiments of the present invention used to illustrate the technical solutions of the present invention, and are not intended to limit the invention, nor are they intended to limit the patent scope of the present invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. These modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention. That is to say, any changes or refinements made to the main design concept and spirit of the present invention that are not of substantial significance, but whose technical problems are still consistent with the present invention, should be included within the protection scope of the present invention. In addition, the direct or indirect application of the technical solutions of the present invention to other related technical fields are similarly included within the patent protection scope of the present invention.

Claims

1. Temperature-sensitive and pH-responsive self-adaptive expandable microspheres for cementing and plugging leaks, characterized in that, It includes a water-absorbing and swelling matrix, a phase change delayed response layer and a silane coupling modified outer layer arranged sequentially from the inside to the outside, with a thermally expanding core dispersed in the phase change delayed response layer; The water-absorbing and swelling matrix is ​​a microsphere core layer composed of a crosslinked copolymer of acrylic acid and acrylamide. Based on a total mass of 100 parts of acrylic acid and acrylamide, the raw material composition of the water-absorbing and swelling matrix is: 55-80 parts of acrylic acid, 20-45 parts of acrylamide, 0.10-0.50 parts of crosslinking agent, 0.20-1.00 parts of initiator, and a pH adjuster to achieve a neutralization degree of 50%-80% for acrylic acid. The phase change delayed response layer is coated on the surface of the water-absorbing and swelling matrix and partially penetrates into the surface pores of the water-absorbing and swelling matrix. The melting point of the phase change delayed response layer is 45~100℃, and the phase change delayed response layer accounts for 5%~25% of the total mass of the swelling microspheres. The thermally expanded core is dispersed in the phase change material of the phase change delayed response layer, and the thermally expanded core accounts for 1% to 10% of the total mass of the expanded microspheres; The silane coupling modified outer layer is the outermost layer of the expanded microspheres, covering the surface of the phase change delayed response layer. It is formed by modifying the surface of the expanded microspheres with a silane coupling agent, and the amount of silane coupling agent is 0.2% to 3.0% of the mass of the expanded microspheres.

2. The expanded microspheres according to claim 1, characterized in that, The mass ratio of acrylic acid to acrylamide is 6:4 to 8:2; the crosslinking agent is N,N'-methylenebisacrylamide; the initiator is any one or more of ammonium persulfate, potassium persulfate, sodium bisulfite-ammonium persulfate redox initiation system or azo initiators, wherein the mass ratio of ammonium persulfate to sodium bisulfite in the sodium bisulfite-ammonium persulfate redox initiation system is 1:0.2 to 1:0.6; the pH adjuster is sodium hydroxide, potassium hydroxide or ammonia.

3. The expanded microspheres according to claim 1, characterized in that, The melting point of the phase change delayed response layer is 55~90℃, and the phase change delayed response layer accounts for 8%~18% of the total mass of the expanded microspheres. The phase change delayed response layer is composed of one or more phase change materials selected from paraffin wax, microcrystalline wax, polyethylene wax, carnauba wax, stearic acid, ethylene-vinyl acetate copolymer wax and composite wax with adjustable melting point.

4. The expanded microspheres according to claim 1, characterized in that, The thermally expandable core accounts for 2% to 6% of the total mass of the expanded microspheres. The thermally expandable core is composed of one or more of the following materials: azo-based thermally decomposed gas-generating material, a bicarbonate-weak acid slow-release gas-generating system, a low-boiling-point organic expanding agent, and thermally expandable microcapsules encapsulated in a phase change material. The bicarbonate-weak acid slow-release gas-generating system is a slow-release system consisting of sodium bicarbonate, potassium bicarbonate, or ammonium bicarbonate, and citric acid, tartaric acid, gluconic acid, adipic acid, or weak acid particles coated with wax / resin. The mass ratio of bicarbonate to weak acid is... The ratio is 1:0.2 to 1:1.5; the thermally expandable microcapsules are microcapsules with acrylonitrile copolymers, vinylidene chloride copolymers, methacrylate copolymers or their complexes as the shell and low-boiling-point organic expanders as the core material, and the initial expansion temperature of the thermally expandable microcapsules is 60~120℃; the azo thermal decomposition gas-producing material is azobisisobutyronitrile, azodicarbonamide, azobisisobutyronitrile or / and modified azodicarbonamide; the low-boiling-point organic expanders are isopentane, isobutane, isooctane, and petroleum ether fraction.

5. The expanded microspheres according to claim 1, characterized in that, The silane coupling agent is one or more of KH550, KH560, and KH570; the amount of silane coupling agent used is 0.5% to 1.5% of the mass of the expanded microspheres.

6. A method for preparing temperature-sensitive-pH dual-responsive self-adaptive expandable microspheres for well cementing and plugging as described in any one of claims 1-5, characterized in that, Includes the following steps: S1. Mix acrylic acid and acrylamide in a mass ratio, add deionized water and stir to dissolve, so that the total mass of acrylic acid and acrylamide accounts for 35% of the total mass of the solution, to obtain a monomer solution; add a crosslinking agent to the monomer solution; then slowly add a pH adjuster to make the degree of neutralization of acrylic acid reach 50%~80%, and the pH of the system after neutralization is 6.0~8.

0. Purify with nitrogen for 10~30 min, then add an initiator to obtain an aqueous phase; S2. Heat the phase change material to a molten state; add the thermal expansion core to the molten phase change material, stir and disperse to form a phase change pre-dispersion liquid containing the thermal expansion core; wherein, the mass ratio of the phase change material to the thermal expansion core is 100:5~100:

40. S3. Using an oily solvent as the continuous oil phase, add an emulsifier and stir until the emulsifier is completely dissolved to obtain the oil phase; wherein, the amount of emulsifier is 1.0%~5.0% of the mass of the continuous oil phase; S4. Slowly add the aqueous phase obtained in step S1 to the oil phase obtained in step S3, controlling the volume ratio of the aqueous phase to the oil phase to be 1:2~1:6; stir and disperse at 300~600 r / min to form a W / O type reverse suspension polymerization system; heat to 55~75℃ and react for 3~6 h to allow acrylic acid and acrylamide to crosslink and copolymerize, forming crosslinked water-absorbing microspheres. S5. After washing, filtering and pre-drying the cross-linked water-absorbing microspheres obtained in step S4 to a water content of 8%~15%, add them to the phase change pre-dispersion liquid containing the thermally expanded core obtained in step S2. The mass ratio of the cross-linked water-absorbing microspheres to the phase change pre-dispersion liquid containing the thermally expanded core is 100:8~100:

22. Stir and coat for 10~60 min. Then cool and solidify to allow the phase change material and the thermally expanded core to adhere to the surface of the water-absorbing and expanding matrix and embed into its surface pores, forming composite microspheres with delayed response function. S6. Immerse the composite microspheres obtained in step S5 in a silane coupling agent solution composed of silane coupling agent, ethanol, and water, wherein the mass of the silane coupling agent accounts for 0.5% to 2.0% of the total mass of the silane coupling agent solution, and the volume ratio of ethanol to water is 90:10; adjust the pH of the silane coupling agent solution to 4 to 5 with acetic acid to promote silane hydrolysis for 20 to 30 min; then let it stand and soak at room temperature for 0.5 to 3 h; after removal, filter, and dry for 6 to 12 h at a temperature 5 to 20°C below the melting point of the phase change delayed response layer to obtain temperature-sensitive-pH dual-response self-adaptive expanding microspheres; S7. The dried expanded microspheres are sieved to obtain expanded microspheres with a particle size of 0.1~1.0 mm.

7. The preparation method according to claim 6, characterized in that, In step S2, the mass ratio of phase change material to thermal expansion core is 100:10 to 100:25; in step S3, the oily solvent is liquid paraffin, white oil, cyclohexane or isooctane, the emulsifier is sorbitan monooleate, and the amount of emulsifier is 1.5% to 3.0% of the mass of the continuous oil phase; in step S4, the volume ratio of aqueous phase to oil phase is 1:3 to 1:

5.

8. The preparation method according to claim 6, characterized in that, In step S4, the mixture is stirred and dispersed at 350~500 r / min, heated to 60~70℃, and reacted for 4~5 h.

9. The preparation method according to claim 6, characterized in that, In step S6: the mass of the silane coupling agent accounts for 1.0% of the total mass of the silane coupling agent solution, and it is left to stand and soak at room temperature for 1-2 hours.

10. The preparation method according to claim 6, characterized in that, In step S7, expanded microspheres with a particle size of 0.2–0.5 mm are obtained.